Pacing the missing piece of the puzzle to high-intensity interval training - Zadow, E. K.; Gordon, N.; Abbiss, C. R.; Peiffer, J. J. (International Journal of Sports Medicine, 2015)
This study examined physiological and perceptual responses to matched work high-intensity interval training using all-out and 2 even-paced methodologies. 15 trained male cyclists performed 3 interval sessions of three 3-min efforts with 3 min of active recovery between efforts. The initial interval session was completed using all-out pacing, with the following 2 sessions being completed with computer- and athlete-controlled pacing in a randomised and semi-counterbalanced manner. Computer- and athlete-controlled intervals were completed at the mean power from the corresponding interval during the all-out trial. Oxygen consumption and ratings of perceived exertion were recorded during each effort. 20 min following each session, participants completed a 4-km time trial and provided sessional rating of perceived exertion. Oxygen consumption was greater during all-out (54.1±6.6 ml/kg.min-1; p<0.01) and athlete-controlled (53.0±5.8 ml/kg.min; p<0.01) compared with computer-controlled (51.5±5.7 ml/kg.min). Total time =85% maximal oxygen consumption was greater during all-out compared to both even-paced efforts. Sessional ratings of perceived exertion were greater after all-out compared to both even-paced sessions. Mean 4-km power output was lower after all-out compared with both even paced intervals. Distribution of pace throughout high-intensity interval training can influence perceptual and metabolic stress along with subsequent performance and should be considered during the prescription of such training.